(untitled) (Research, Society and Development, 2020)
Biotransformations are reactions carried out by microorganisms that lead to changes in the structures of organic compounds, among the biotransformations there are bioreductions. Bioreductions are of great interest to the pharmaceutical and food industries, as they almost always lead to the formation of enantiomerically pure compounds. Thus, this work aimed to verify the ability of the fungus Lasiodiplodia pseudotheobromae in bioreduce α,β-unsaturated carbonyl compounds. Compounds (3E)-4-(2-methoxy-phenyl)-but-3-en-2-one (1), (1E, 4E)-1,5-diphenyl-pent-1,4-dien-3-one (2) and (1E, 4E)-1,5-bis-(2-methoxy-phenyl)-penta-1,4-dien-3-one (3) were used as substrates. The reactions were carried out on an orbital shaker for 8 days at room temperature. The products formed were characterized by analytical thin layer chromatography (ATLC), high performance liquid chromatography (HPLC) and hydrogen nuclear magnetic resonance (1H NMR). For all products formed was observed reduction in double bonds C=C and C=O leading to the formation of the respective alcohols. This is the first report of biotransformation reactions using the fungus Lasiodiplodia pseudotheobromae.